Entre caixa preta e cubo branco: o vídeo nos espaços das artes plásticas - Adolfo Enrique Cifuentes Porras (2010)
This thesis explores a broad range of aspects related to the transference of the moving image from the Black Box of the movie theater to the White Cube of the museum gallery. Given the fact that (by definition) the moving-image is sequencial in time, the storytelling of cinema was, for a long time, the natural field of exploration of its creative possibilities. However, starting a few decades ago, a steady but definitive shift has been taking place. The moving image is going into the gallery and the museum. Two clearly distinct regimens of attention and gaze overlap each other: the sitting viewer in his seat and the walking visitor in the gallery, as well as the fixed and the time-based image. Several other juxtapositions take place in this relocation: the materialityspatialityof painting, sculpture and architecture with the narrative transitoriness of the audiovisual image. In this manner, the materiality of the different technological supports intrinsically related to the production of the moving image establishes dialogues with the museums function ofpreserving memory. This materiality of the technological supports also dialogues with the physical presence and spatial experience associated with the traditional field of the Fine Arts. These multiple intersections structure this particular research.